2009
DOI: 10.1177/0021955x09104472
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Modulus of Symmetric and Asymmetric Structural Foams

Abstract: In this work, the preparation and characterization of symmetric and asymmetric structural foams is presented. Using low-density polyethylene and modified azodicarbonamide, a compression molding technique is presented to produce structural foams while controlling the skin thickness on both sides. The resulting foams were characterized in terms of foam density, skin thickness, and flexural modulus. It was found that foams having equal skin thickness on each side have the same apparent flexural modulus irrespecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…On the other hand, all the asymmetric samples, with the exception of EM-30, have a ratio significantly different than unity. This supports once again our previous results: asymmetric foams have asymmetric mechanical properties in flexion (6)(7)(8)11) . This is due to an asymmetric distribution of the material inside the foams.…”
Section: Flexural Modulussupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, all the asymmetric samples, with the exception of EM-30, have a ratio significantly different than unity. This supports once again our previous results: asymmetric foams have asymmetric mechanical properties in flexion (6)(7)(8)11) . This is due to an asymmetric distribution of the material inside the foams.…”
Section: Flexural Modulussupporting
confidence: 91%
“…One recent example is asymmetric structural foams where skin thickness is not equal on both sides of the foam. (6) In this case, it was shown that loading direction has an important effect on mechanical properties like flexural modulus and impact strength (7)(8) . This phenomenon is directly related to stress distribution inside the material, which is function of density.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most of the asymmetric samples have apparent flexural modulus ratio outside this range. For example, sample 14 has a ratio as low as 0.68, which is much lower than any reported value so far [18,[20][21][22][24][25][26]. In fact, flexural strength is a function of load direction for asymmetric samples because the neutral axis is no longer at the geometric center of the sample.…”
Section: Flexural Modulusmentioning
confidence: 61%
“…31 This behavior is usually associated with highly reduced densities and low mechanical properties of foamed polymers. 35 So the elastic modulus of MMM is controlled by two competing factors: foaming which highly reduces densities and mechanical properties, as well as the presence of solid SiO 2 nanoparticles yielding higher mechanical properties. The interaction between the polymer matrix and inorganic particles is very important and can also affect the mechanical properties.…”
Section: Resultsmentioning
confidence: 99%